Unique considerations in the assessment and management of traumatic brain injury in older adults - Depreitere, Bart; Becker, Clemens; Ganau, Mario; Gardner, Raquel C; Younsi, Alexander; Lagares, Alfonso; Marklund, Niklas; Metaxa, Victoria; Muehlschlegel, Susanne; Newcombe, Virginia F J; Prisco, Lara; van der Jagt, Mathieu; et al. (The lancet, 2025)
The age-specific incidence of traumatic brain injury in older adults is rising in high-income countries, mainly due to an increase in the incidence of falls. The severity of traumatic brain injury in older adults can be underestimated because of a delay in the development of mass effect and symptoms of intracranial haemorrhage. Management and rehabilitation in older adults must consider comorbidities and frailty, the treatment of pre-existing disorders, the reduced potential for recovery, the likelihood of cognitive decline, and the avoidance of future falls. Older age is associated with worse outcomes after traumatic brain injury, but premorbid health is an important predictor and good outcomes are achievable. Although prognostication is uncertain, unsubstantiated nihilism (eg, early withdrawal decisions from the assumption that old age necessarily leads to poor outcomes) should be avoided. The absence of management recommendations for older adults highlights the need for stronger evidence to enhance prognostication. In the meantime, decision making should be multidisciplinary, transparent, personalised, and inclusive of patients and relatives.
Gesehen am 22.10.2025